The Effects of Business Cycle and Debt Maturity on a Firm’s Investment in Fixed Assets - pari rashedi; Hamid reza Bazzaz zadeh (پژوهش‌های تجربی حسابداری, 2017)
This research is aimed to investigate of the effects of business cycle and debt maturity on a firm’s investment in fixed assets. To do this, the financial information of 113 industrial firms listed in Tehran Stock Exchange during the period from 2004 to 2014 (1243 firm-years) is examined and to test the hypotheses, the method of regression analysis based on pooled data is used. The results show that there is a significant positive relation between business cycle and investment in fixed assets, and a significant negative relation between debt maturity and investment in fixed asset. Additionally, the results show that business cycle has significant positive effect on the relation between debt maturity and investment in fixed assets. Extra tests on industry levels (medical materials and productions, car and pieces structure, chemical materials and productions, metals, tile and ceramic) show that business cycle is effective on debt maturity and investment in fixed assets only in chemical industry not other industries.